Occupational risk factors for idiopathic pulmonary fibrosis in Southern Europe: a case-control study - Giulia Paolocci; Ilenia Folletti; Kjell Torén; Magnus Ekström; Marco Dell’Omo; Giacomo Muzi; Nicola Murgia (2018)
Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive fibrosing interstitial pneumonia of unknown cause associated with the histopathologic and/or radiologic pattern of usual interstitial pneumonia (UIP). Occupational risk factors have been proposed to be associated with UIP. The aim of this case-control study is to evaluate the relationship between UIP pattern and occupational exposure in Southern Europe.Sixty nine cases with a UIP radiological pattern at CT-scan were selected from a clinical database of the University Hospital of Perugia, Umbria, between January 2010 and December 2013. Controls (n = 277) not reporting doctor diagnosed pulmonary fibrosis, were ascertained casually among general population from the same catching area of cases. Data were collected by a questionnaire used previously in a similar study. Logistic regression models, adjusted for gender, age and smoking, were performed to evaluate the association between UIP and occupational exposure.Farmers, veterinarians and gardeners (OR = 2.73, 95%CI = 1.47-5.10), metallurgical and steel industry workers (OR = 4.80, 95%CI = 1.50-15.33) were occupations associated with UIP. Metal dust and fumes and organic dust were risk factors for UIP. Increasing the length of occupational exposure in jobs at risk of pulmonary fibrosis, increased the risk of having UIP.This case control study confirm partially the results from previous similar studies. Some discrepancies could be explained by the different geographical origins of the population under study, reflecting also different occupational exposures.